Catalytic conversion of waste lubricating oil to liquid fuels over Fe/activated carbon, CoMo/Al2O3 and HZSM-5 Catalysts - Amnat Permsubscul (Chulalongkorn University, 2013)
Thesis (Ph.D.)--Chulalongkorn University, 2004